Geometrical structures for radiation biology research as implemented in the TOPAS-nBio toolkit. (6th September 2018) - McNamara, Aimee L; Ramos-Méndez, José; Perl, Joseph; Held, Kathryn; Dominguez, Naoki; Moreno, Eduardo; Henthorn, Nicholas T; Kirkby, Karen J; Meylan, Sylvain; Villagrasa, Carmen; Incerti, Sebastien; Faddegon, Bruce; et al.
Abstract: Computational simulations, such as Monte Carlo track structure simulations, offer a powerful tool for quantitatively investigating radiation interactions within cells. The modelling of the spatial distribution of energy deposition events as well as diffusion of chemical free radical species, within realistic biological geometries, can help provide a comprehensive understanding of the effects of radiation on cells. Track structure simulations, however, generally require advanced computing skills to implement. The TOPAS-nBio toolkit, an extension to TOPAS (TOol for PArticle Simulation), aims to provide users with a comprehensive framework for radiobiology simulations, without the need for advanced computing skills. This includes providing users with an extensive library of advanced, realistic, biological geometries ranging from the micrometer scale (e.g. cells and organelles) down to the nanometer scale (e.g. DNA molecules and proteins). Here we present the geometries available in TOPAS-nBio.